Dysregulation of murine immune functions on inhalational exposure to ammonia, dimethyl disulfide, 3-methylindole, or propionic acid. (April 2021) - Kim, HyeonJi; Song, EunSeob; Lee, JaeHee; Gautam, Ravi; Shin, SoJung; Cho, AhRang; Kim, YeonGyeong; Yang, SuJeong; Jo, JiHun; Acharya, Manju; Maharjan, Anju; Kim, ChangYul; et al.
Animal husbandry workers are exposed to various malodorous compounds in the workplace. Although these compounds cause severe nuisance, no systemic investigation of their effects on the immune system has been conducted. To address this issue, we evaluated the effects of inhalational exposure to ammonia, dimethyl disulfide, 3-methylindole (3-MI), and propionic acid (PA), representing four major groups of malodorous compounds, on humoral and cellular immunity in mice. Mice were exposed to the substances (low dose: 10 µL and high dose: 200 µL) for 10 min/day for 4 weeks in a modified standard mouse cage. Neutrophil% and splenic cytotoxic T cell% were significantly lower in the high-dose ammonia group than in the vehicle control. Exposure to ammonia and 3-MI increased immature thymic T lymphocyte% relative to control and concomitantly decreased both mature helper and cytotoxic T-cell populations in the thymus. In the ammonia exposure group, levels of serum immunoglobulin E and immunoglobulin A were elevated, and the IgG2a:IgG1 ratio in the serum was reduced in a dose-dependent manner. Splenic natural killer cell activity was significantly less in the PA exposure group than in the control. Overall, our findings suggest that inhalational exposure to these malodorous substances disturbs immune homeostasis in vivo .